Nature based solutions for sustainable cities: A review of the state of the art of green roof research - Gutierrez, Agustina (2025)
The study of green roofs is an interdisciplinary field recognized for its eco-friendly roofing solutions. Green roofs offer ecological, economic, and societal benefits, making them an ef- fective way to address urbanization's negative impacts. This review explores the evolution of green roofs from ancient prototypes to modern innovations. Using the Google Scholar da- tabase, we conducted a bibliometric analysis of 50 articles to assess publication rates in the "green roof " area. Descriptive statistics were used to identify key contributors, ecosystem ser- vices, research methodologies, and spatial scales in green roof studies. Our analysis showed a rise in research on green roof technology in the early 21st century, with the United States and China leading this research. Urban heat island mitigation emerged as a primary research focus for green roofs, with cities being the most studied spatial scale. The most common keywords were "green roofs," "urban," and "energy." This study thoroughly reviews the past and present state of green roofs, showcasing a range of indicators that provide valuable insights for future research and emerging trends in the area.